2004
DOI: 10.1091/mbc.e03-08-0630
|View full text |Cite
|
Sign up to set email alerts
|

The FAM Deubiquitylating Enzyme Localizes to Multiple Points of Protein Trafficking in Epithelia, where It Associates with E-cadherin and β-catenin

Abstract: Ubiquitylation is a necessary step in the endocytosis and lysosomal trafficking of many plasma membrane proteins and can also influence protein trafficking in the biosynthetic pathway. Although a molecular understanding of ubiquitylation in these processes is beginning to emerge, very little is known about the role deubiquitylation may play. Fat Facets in mouse (FAM) is substrate-specific deubiquitylating enzyme highly expressed in epithelia where it interacts with its substrate, ␤-catenin. Here we show, in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
86
1
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(90 citation statements)
references
References 58 publications
2
86
1
1
Order By: Relevance
“…USP9X has been implicated in many different biological processes, including protein trafficking (45) and tight junction biogenesis in epithelial cells (70), regulation of the transforming growth factor-␤ pathway (51), and chromosome alignment and segregation (71). In addition, it has been shown that USP9X modulates the levels of proteins such as the following: ␣-synuclein (72), a protein involved in the pathogenesis of Parkinson disease; MCL1, an anti-apoptotic protein that is overexpressed in some types of cancer (73); some protein kinases involved in stress responses and cellular energy homeostasis (65,74); and some ubiquitin-ligases, such as MARCH7 and Itch (75,76).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…USP9X has been implicated in many different biological processes, including protein trafficking (45) and tight junction biogenesis in epithelial cells (70), regulation of the transforming growth factor-␤ pathway (51), and chromosome alignment and segregation (71). In addition, it has been shown that USP9X modulates the levels of proteins such as the following: ␣-synuclein (72), a protein involved in the pathogenesis of Parkinson disease; MCL1, an anti-apoptotic protein that is overexpressed in some types of cancer (73); some protein kinases involved in stress responses and cellular energy homeostasis (65,74); and some ubiquitin-ligases, such as MARCH7 and Itch (75,76).…”
Section: Discussionmentioning
confidence: 99%
“…45). Indeed, USP9X presents a Stokes radius of 7.3 nm, eluting from the SEC column as if it were a 550-kDa globular/spherical protein (see supplemental Fig.…”
Section: Figure 1 Dub Acting On Ub-pex5 Is a Cytosolic Protein Amentioning
confidence: 99%
“…Although the deubiquitinase FAM (USP9X) is able to target and stabilize ␤-catenin, it has been suggested to be mainly involved in the trafficking of ␤-catenin and E-cadherin in epithelia (19). USP14 was also found to be overexpressed in lung adenocarcinoma and able to stabilize ␤-catenin; however, it was shown to work by directly targeting the upstream regulator Dishevelled (Dvl) (20,21).…”
mentioning
confidence: 99%
“…128 Later, it was established that USP9x positively regulates the TGFβ signaling pathway by targeting Smad4 for deubiquitination. 129 Monoubiquitination of Smad4 impedes its association with phosphorylated Smad2, which is a decisive step in the activation of the TGFβ signaling pathway.…”
mentioning
confidence: 99%